"Greening" the economy is the solution? - Bejarano, Rodolfo (2014)
One of the recurring themes in these days of negotiations for the COP20 in our country is the Green Economy, an idea that has been raised by various sectors as the solution to environmental problems and as the basis for tackling climate change at a global level. However, this is not a new proposal that has been created on the occasion of the twentieth conference of parties to the United Nations Framework Convention on Climate Change, but neither is much known about what is sought with it and how it would be implemented. Although the color green automatically connects us with the attitude of human beings towards the care of the environment and natural resources, it could also refer to the color of the US currency, and it is precisely in this aspect where the criticism of civil society sectors that see the green economy as the continuity of the current system and, therefore, would not constitute a real solution to the global problem is focused.